Dysmenorrhea in Adolescents: How to approach: A Review Article - Zeba, Dilruba; Benarjee, Shipra; Biswas, Rajib; Akter, Sajeda; Rahman, Raiyan Muhibur (Bangabandhu Sheikh Mujib Medical College Journal, 2024)
Dysmenorrhea refers to recurrent pelvic pain during menstruation in sufficient magnitude, which incapacitates a woman’s day-to-day activities. It is the most common gynecological complaint among adolescents. It negatively impacts their quality of life, attendance at school or work and mental health. Most adolescents experiencing dysmenorrhea have primary dysmenorrhea without having any pelvic pathology. If a girl does not feel clinical improvement within 3-6 months of empiric treatment with nonsteroidal anti-inflammatory drugs, secondary dysmenorrhea should be kept in mind and exploration of the cause of secondary dysmenorrhea should be done. Our objective was to review the current knowledge regarding the pathophysiology of dysmenorrhea and to summarize the approach in the diagnosis and management in specific adolescent groups. We selected adolescents as their psychosomatic factors like anxiety, tension adversely influence their pain threshold. We reviewed the recent article written on dysmenorrhea, which has been published in different medical literature. At the same time, different guidelines and treatment protocols have been reviewed. Adolescents are more vulnerable to dysmenorrhea. They are suffering mostly from primary dysmenorrhea, but pelvic pathology should be kept in mind, especially endometriosis and Mullerian abnormalities. Non-steroidal anti-inflammatory drugs (NSAIDs) and oral contraceptive pills (OCP) are the first-line treatment. Special emphasis should be given to improving their mental strength. Bangabandhu Sheikh Mujib Med. Coll. J. 2024;3(1):44-48